2014
DOI: 10.1037/a0037550
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic comparison of the effectiveness of methadone and two sublingual formulations of buprenorphine on maintenance treatment outcomes: Findings from a retrospective multisite study.

Abstract: Comparable rates of illicit drug use at 6 months may be expected irrespective of maintenance medication, while increased retention may be expected for patients maintained on methadone relative to those maintained on Suboxone or Subutex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Additional differences in clinical, psycho-patholological and sociodemographic characteristics, as well co-morbid medical and psychiatric diagnoses, use of concomitant psychotropic medications, and healthcare service use between these two groups have been noted in previous studies (Barnett, 2009; Baxter et al, 2011; Fingerhood et al, 2014; Gerra et al, 2004; Hansen et al, 2013; Maremmani et al, 2011, 2007; Oliva et al, 2012, 2013; Proctor et al, 2014; Stein et al, 2012). However, a detailed national level comparative study of the characteristics of patients who receive each of these treatments has yet to be published despite the dramatic change in the nature of OAT utilization in the United States during the past decade.…”
Section: Introductionsupporting
confidence: 55%
“…Additional differences in clinical, psycho-patholological and sociodemographic characteristics, as well co-morbid medical and psychiatric diagnoses, use of concomitant psychotropic medications, and healthcare service use between these two groups have been noted in previous studies (Barnett, 2009; Baxter et al, 2011; Fingerhood et al, 2014; Gerra et al, 2004; Hansen et al, 2013; Maremmani et al, 2011, 2007; Oliva et al, 2012, 2013; Proctor et al, 2014; Stein et al, 2012). However, a detailed national level comparative study of the characteristics of patients who receive each of these treatments has yet to be published despite the dramatic change in the nature of OAT utilization in the United States during the past decade.…”
Section: Introductionsupporting
confidence: 55%
“…Recent naturalistic data from a large study comparing the effects of methadone and BUP (both formulations) also found a higher retention rate among methadone patients than patients on BUP or BUP/NLX. 61 With respect to the two BUP formulations, patients in the BUP/NLX group showed a significantly longer average retention than the BUP group. The rates of illicit drug use at 6 months were similar across medication groups.…”
Section: Buprenorphine In Opioid Maintenance Treatment: Overviewmentioning
confidence: 92%
“…opioid agonist treatment (OAT)], coverage of OAT programmes remains low in many settings . Additionally, among those who access OAT, only a minority are retained on treatment, with some studies documenting 6‐month retention rates as low as 20% . This is concerning, as discontinuation from OAT has been associated with increased mortality risk .…”
Section: Introductionmentioning
confidence: 99%